Trois perspectives lesbiennes féministes articulant le sexe, la sexualité et les rapports sociaux de sexe : Rich, Wittig, Butler - Brossard, Louise (Université du Québec à Montréal, 2004)
Keywords: IREF; approches et analyses; discipline; genre; hétérosexisme; identités; identités LGBTQIA2+; lesbianisme; mémoires/thèses; rapports sociaux de sexe; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques

Pornography, Women and Feminism: Between Pleasure and Politics - Ciclitira, Karen (Sexualities, 2004)
This article draws on a qualitative research study which set out to explore women’s experiences and views of pornography within the broader context of conflicting feminist positions on pornography. The research methodology posed an implicit criticism of the kind of ‘findings’ familiar from mainstream psychological research: semi-structured interviews were conducted with women from diverse backgrounds in the UK, and feminist theory and discourse analysis were used to inform interpretation of their accounts. Although the question of feminism was not explicitly raised by the interviewer, it emerged as a recurrent theme in interviews, with interviewees suggesting that the feminist anti-porn stance in particular has influenced their perspective on pornography. Their accounts show that women’s experiences are variegated, individual and complex, and that discourses of pornography and feminism may be negotiated in unpredictable ways.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; féminisme pop; pornographie; premier cycle; psychologie; périodes historiques; recherche qualitative; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; sex1911; sexualité; thématiques

Aberrations in Black: Toward a queer of color critique - Ferguson, Roderick A. (Critical American studies series, 2004)
A hard-hitting look at the regulation of sexual difference and its role in circumscribing African American culture. The sociology of race relations in America typically describes an intersection of poverty, race, and economic discrimination. But what is missing from the picture—sexual difference—can be as instructive as what is present. In this ambitious work, Roderick A. Ferguson reveals how the discourses of sexuality are used to articulate theories of racial difference in the field of sociology.
Keywords: amériques; approches et analyses; cours; discipline; discours dominant; fem1000; fem3300; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; queer of color; racisme; ressource en ligne; régions géographiques; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Dictionnaire critique du féminisme - Hirata, Helena (Politique d'aujourd'hui, 2004)
Avortement et contraception, citoyenneté, division sexuelle du travail et rapports sociaux de sexe, domination, famille, féminité-masculinité-virilité, harcèlement sexuel, histoire (sexuation de l'), maternité, migration, mixité, mondialisation, mouvements féministes, parité , patriarcat (théories du), précarisation sociale, prostitution, sexualité, transmissions intergénérationnelles, syndicats, travail domestique, violences.dictionnaire est de changer la façon commune de penser " : l'ambition de Diderot est reprise avec force par les auteurs de ce parcours historique etcritique duféminisme . Cette volonté éditoriale s'exprime dans le choix typologique des entrées : des concepts nouveaux issus de la théorisation féministe, des champs d'intervention des luttes féministes, des notions transversales d'économie et de sociologie du travail.Dictionnaire théorique et politique, pluriel et engagé, cet ouvrage se veut aussi un texte de conviction et d'explication.
Keywords: 1900-1999; approches et analyses; avortement; corps; cours; cycles supérieurs; dictionnaire critique; discipline; europe; fem1000; fem7000; france; har4600; histoire et politique; interdisciplinarité; justice reproductive; lit2815; lit3220; lit3495; militance; outils; ouvrages de références; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sexualité; sociologie; thématiques; travail

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Feminist constructions, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

La grande arnaque : sexualité des femmes et échange économico-sexuel - Tabet, Paola (Bibliothèque du féminisme, 2004)
Dans la majorité des sociétés connues, la sexualité apparaît comme un échange asymétrique et non réciproque entre hommes et femmes, une compensation masculine pour une prestation féminine, un paiement qui peut revêtir les formes les plus variées en échange d'une sexualité transformée en service. Comment se fait-il que les hommes, même plongés dans les situations les plus misérables, peuvent se payer le service sexuel d'une femme - alors que non seulement les femmes n'ont pas, sauf exception, cette possibilité mais de plus n' ont même pas droit à leur propre sexualité ?
Keywords: EDI; approches et analyses; cours; cycles supérieurs; discipline; division sexuelle du travail; ethnologie; fem1000; fem7000; inégalités; lit3220; premier cycle; rapports sociaux de sexe; sciences; sciences humaines; sexualité; systèmes d'oppressions; thématiques; épistémologie